UPAYA PENCEGAHAN PENULARAN COVID-19 MELALUI EDUKASI & VAKSINASI DI SENTRA VAKSIN STIKES HORIZON KARAWANG - Novianti, Rima; Nurjanah, Uun (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
The respiratory system is attacked by COVID-19, which might be fatal. COVID-19 was been categorized as a global pandemic by WHO on March 9, 2020. The government has established rules to restrict community activities, implement health standards, and provide vaccines since COVID-19 transmission is very simple, causing the increase in positive COVID-19 cases to skyrocket. According to the findings of in-depth interviews with community leaders in Karawang Regency, the majority of the population still lives a traditional lifestyle, and many people refuse to receive the COVID-19 vaccine because they lack information, making it difficult for them to distinguish between information based on true or false facts. As a result, the public perceives the programs offered to combat the pandemic as being less significant. Therefore, the goal of this effort is to reinforce knowledge of COVID-19 and transmission prevention through education and immunization. The activity's results demonstrated that, in line with the public's growing interest in immunization and adherence to health protocols as evidence of a growing general understanding of COVID-19 transmission and prevention, the implementation of education and vaccination to prevent COVID-19 transmission increased. In the Karawang Regency, this has a cascading effect on establishing COVID-19 herd immunity.